Les Glasgow Rent Strikes de 1915 ou quand la désobéissance civile des femmes contraint le législateur - Olivier Esteves (Revue LISA)
The outbreak of World War I in 1914 generated a massive influx of workers into the Clyde area, a hugely strategic region for heavy industry (shipyards, but also ammunition factories). This influx caused rents to rise in a certain number of districts, mostly around the factories and the shipyards. In order to protest against such grossly unfair increases, the women of Glasgow and their families decided to refuse to pay the new rents. They argued that they too contributed actively to the war effort, and that, by imposing rent hikes, the landlords of Glasgow and their factors implicitly sided with the German foe, by weakening a portion of the population so instrumental in supplying the British armed forces on the continent. After several months of actively sustained civil disobedience, Parliament passed a law that fixed rents until the end of the conflict. But in actual fact the Glasgow Rent Strikes generated certain changes that were to go way beyond the peculiar context of the Great War.